Disease resistance features of the executor R gene Xa7 reveal novel insights into the interaction between rice and Xanthomonas oryzae pv. oryzae - He, Lumei; Liu, Pengcheng; Mei, Le; Luo, Huichao; Ban, Tingxuan; Chen, Xifeng; Ma, Bojun (Frontiers in Plant Science, 2024)
Bacterial blight (BB), caused by Xanthomonas oryzae pv. oryzae (Xoo), is a widespread and destructive disease in rice production. Previously we cloned an executor R gene, Xa7, which confers durable and broad-spectrum resistance to BB. Here, we further confirmed that the transcription activatorlike effector (TALE) AvrXa7 in Xoo strains could directly bind to the effector binding element (EBE) in the promoter of the Xa7 gene. Other executor R genes (Xa7, Xa10, Xa23 and Xa27) driven by the promoter of the Xa7 gene could be activated by AvrXa7 and triggered the hypersensitivity response (HR) in tobacco leaves. When expression of the Xa23 gene was driven by the Xa7 promoter, the transgenic rice plants displayed a similar resistance spectrum as the Xa7 gene, demonstrating that the disease resistance characteristics of executor R genes are mainly determined by their induction patterns. Xa7 gene is induced locally by Xoo in the infected leaves and its induction not only inhibited the growth of incompatible strains, but also enhanced resistance of rice plants to compatible strains, which overcame the shortcomings of its racespecific resistance. Transcriptome analysis of the Xa7 gene constitutive expression rice plants displayed that Xa7-mediated disease resistance was related to the biosynthesis of lignin and thus enhanced resistance to Xoo.Overall, our results provided novel insights and important resources for further clarifying the molecular mechanisms of the executor R genes.